Solvent- and guest-responsive supramolecular self-assembly of 1,3,5-tris(10-carboxydecyloxy) benzene by scanning tunneling microscopy - Cui, Lihua; Miao, Xinrui; Xu, Li; Deng, Wenli (Applied surface science, 2014)
•TCDB can entrap solvent molecules or π-electron-conjugated guest molecules.•We calculate hydrogen bonding which is crucial to stabilize the assembly networks.•Structural properties rely on the solvent- and guest-responsive assembly.•Kinetics and thermodynamics explain the morphology character of polarity. Two-dimensional hydrogen-bonded networks formed in the self-assembly of 1,3,5-tris(10-carboxydecyloxy) benzene (TCDB) show regular solvent- and guest-induced supramolecular structural properties, which have been presented by scanning tunneling microscopy at the liquid–solid interface at ambient conditions. TCDB acting as a host template can entrap solvent molecules or π-electron-conjugated guest molecules to fabricate the flexible co-adsorption architectures, which are subject to the balance between the hydrogen bonding of the host lattice and the van der Waals forces between the host and the guest molecules. Hydrogen bonding among TCDB molecules is crucial to stabilize the host networks to settle the system into a global minimum of Gibbs free energy. We also find a strong correlation between the structural parameters and the physical properties of the solvent. Statistical analysis shows that the unit cell volume of TCDB dissolved in nonpolar 1-phenylotane and n-tetradecane shrank significantly compared with that of host–guest system, which fully reflects the coadsorption effect of nonpolar solvent molecules. Our results identify that the kinetic effect of adsorption/desorption as well as the solvent viscosity comes into play in tuning the two-dimensional self-assembled structures. Furthermore, mechanical calculations demonstrate that TCDB incline to adsorb with a larger dipole configuration in nonpolar solvents due to its dissolvability. It is believed that the results are of significance to supramolecular host–guest chemistry and surface science.